Effectiveness of Emotion-Focused Therapy on Anger Expression and Forgiveness in Divorced Women - Maisarah, Syarifah; Chen, Mei-Ling (Psychology of Woman Journal, 2024)
Objective: This study aimed to examine the effectiveness of Emotion-Focused Therapy (EFT) on anger expression and forgiveness in divorced women. Methods and Materials: The study was designed as a randomized controlled trial involving 30 divorced women from Taiwan, who were randomly assigned to either an intervention group (n = 15) receiving eight weekly sessions of EFT or a control group (n = 15) receiving no intervention. Each session lasted between 60–90 minutes and was delivered in a group format. Both groups were assessed at three time points: pre-test, post-test, and five-month follow-up. Standardized instruments were used to assess anger expression and forgiveness. Data were analyzed using repeated measures analysis of variance (ANOVA) to evaluate within- and between-group effects over time, and Bonferroni post-hoc tests were used to identify specific changes across time points. SPSS-27 software was used for all statistical analyses. Findings: Repeated measures ANOVA revealed significant time × group interactions for both anger expression (F(2, 84) = 30.04, p < .001, η² = .52) and forgiveness (F(2, 84) = 34.89, p < .001, η² = .56), indicating that changes over time were significantly greater in the EFT group compared to the control group. Bonferroni post-hoc tests showed significant reductions in anger expression (p < .001) and significant increases in forgiveness (p < .001) from pre-test to post-test in the EFT group, with these gains sustained at the five-month follow-up. Conclusion: The findings support the effectiveness of Emotion-Focused Therapy in reducing anger expression and enhancing forgiveness among divorced women. EFT appears to be a valuable intervention for promoting emotional regulation and psychological healing following marital dissolution.